Conventional Home Loan and Islamic Home Financing in Comparative Perspective - Umardani, Dwi (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
This article aims to comparatively discuss conventional home loan (Kredit Perumahan Rakyat/KPR) and Islamic home financing (Pembiayaan Pemilikan Rumah Syariat/PPRS), locating in Bank Central Asia (BCA) and Bank Syariah Mandiri (BSM). Qualitative narrative of formal procedural system of owning home of the mortgages critically analyzed aiming to get clear-cut the differences both loans. This paper confirms that BCA uses the interest system in providing mortgage (KPR) and does not concern on the use of the funds. BSM generally has implemented murabaha scheme (deferred payment sale). For the late paying installments, both banks have applied quite different procedure systems.Keywords: mortgages, home loan, KPR, PPRS